Internalization of Moral and Spiritual Values in Arabic Language Textbooks: A Content Analysis of Grade X Materials - Achmad Satori; Toto Edidarmo; N. Lalah Alawiyah; Nirwan Anwar (ALSINATUNA, 2025)
This study aims to identify and analyze moral and spiritual values embedded in the Qirā’ah texts of the Grade X Arabic Language Textbook for Madrasah Aliyah and to examine their potential internalization in Arabic language learning. The study employs a descriptive qualitative approach using content analysis as the primary analytical framework. The main data source consists of six Qirā’ah instructional units, while limited classroom observations and semi-structured interviews with Arabic language teachers were used for contextual and methodological triangulation. Data validity was ensured through source and method triangulation, member checking, and the application of naturalistic trustworthiness criteria, including credibility, transferability, dependability, and confirmability. Data analysis followed the stages of data reduction, data display, and conclusion drawing as proposed by Miles, Huberman, and Saldaña. The theoretical framework integrates perspectives of Islamic spirituality (al-Faruqi, Nasr, Saritoprak) with ethical and character theories (MacIntyre, Shapiro, Rachels & Rachels). The findings indicate that moral values are consistently embedded across all Qirā’ah texts, particularly through representations of social ethics, personal responsibility, discipline, cooperation, and everyday conduct. Spiritual values appear more selectively and are mainly associated with religious awareness, worship practices, Qur’anic references, and ethical principles grounded in Islamic teachings. Overall, the study demonstrates that Qirā’ah texts function not only as tools for developing linguistic competence but also as meaningful media for character education and Islamic spiritual development, supporting the objectives of Islamic education and the national curriculum framework.